‘Your Story is Told, Your Issue is Handled’ The Myth of Social Activity Corporate Storytelling in English-Speaking Business Communication in the Age of Technically Mediated Orality - Haase, Fee-Alexandra (PRISMA.COM, 2011)
In this article we focus on a specific form of business communication called storytelling. Storytelling is practiced in marketing, PR, and journalism. Storytelling is a common genre of oral communication also implemented into written texts. Storytelling in business communication is a form of persuasive communication directed towards the consumer. The story connects the product and the consumer. 'Tua fabula narritur, tua res agitur.' or 'Your story is told, your issue is handled'. is the maxim of this identification effect. Storytelling is a narrative mode that in several ways binds the consumer to the product. The most effective elements of storytelling are evidence and the direct approach of the consumer. The narrative mode is a special mode of business communication.